Probiotic potential and safety assessment of bacteriocinogenic Enterococcus faecalis CAUM157 - Arxel G. Elnar; Geun-Bae Kim (Frontiers in Microbiology)
IntroductionOver the past few years, the genus Enterococcus has been implicated as both probiotic and pathogenic bacteria, making it challenging to introduce enterococcal probiotic candidates. Based on rigid case-by-case analysis, some enterococcal strains have been developed as probiotics, exhibiting various beneficial activities that promote the health of the host. In this study, the probiotic potential of Enterococcus faecalis CAUM157 (KACC81148BP), isolated from raw cow’s milk, was examined, leveraging its bacteriocin production for potential control of pathogenic and spoilage-associated bacteria.MethodsThe probiotic properties of Enterococcus faecalis CAUM157 were evaluated using a combination of genomic analyses and in vitro assays. In addition, various in silico analyses were performed to assess the safety of the strain and correlate its genotype with the observed phenotypic characteristics.Results and discussionGenomic analyses revealed virulence factors associated with adhesion, biofilm formation, and anti-phagocytosis. Various enzymes and antimicrobial resistance genes that confer resistance to aminoglycosides, lincosamides, macrolides, streptogramins A and B, and tetracyclines were also identified. Although generally regarded as detrimental, virulence factors are crucial to colonization, niche establishment, and subsequent manifestation of the beneficial effects of the strain, as evident in other probiotic lactic acid bacteria. Notably, CAUM157 was sensitive to clinically important antibiotics like ampicillin (MIC, 4.0 µg/mL) and vancomycin (MIC, 1.0 µg/mL), congruent with its ST21 MLST typing. CAUM157 survived in acidic conditions (pH 3.0 and pH 2.0) with 100.72 ± 0.20% and 97.28 ± 2.19% survival rates, respectively, and showed high survival rates when exposed to 0.3% (104.16 ± 3.42%) and 0.5% (90.65 ± 1.22%) bile extract, attributed to the enzymatic activity of bile salt hydrolase. CAUM157 also exhibited robust auto-aggregation and co-aggregation when interacting with Listeria monocytogenes. Finally, the ability to produce a broad-spectrum bacteriocin in conjunction with other factors indicates a potentially efficient mechanism for mitigating the pathogenicity of detrimental bacteria, including Staphylococcus aureus, Clostridium perfringens, and Streptococcus mutans.ConclusionEnterococcus faecalis CAUM157 survived exposure to artificial gastric conditions and exhibited robust auto- and co-aggregation capacity with Listeria. Additionally, the ST21 MLST typing of the strain, along with the identified niche factors and the lack of resistance to vancomycin and ampicillin, highlights its apparent safety. The results of this study suggest that strain CAUM157 may be a potential probiotic candidate in the food and feed industries.